The Index of Cognitive Activity as a Measure of Cognitive Processing Load in Dual Task Settings - Vogels, Jorrig; Demberg, Vera; Kray, Jutta (Frontiers in Psychology, 2018)
Increases in pupil size have long been used as an indicator of cognitive load. Recently, the Index of Cognitive Activity (ICA), a novel pupillometric measure has received increased attention. The ICA measures the frequency of rapid pupil dilations, and is an interesting complementary measure to overall pupil size because it disentangles the pupil response to cognitive activity from effects of light input. As such, it has been evaluated as a useful measure of processing load in dual task settings coordinating language comprehension and driving. However, the cognitive underpinnings of pupillometry, and any differences between rapid small dilations as measured by the ICA and overall effects on pupil size are still poorly understood. Earlier work has observed that the ICA and overall pupil size may not always behave in the same way, reporting an increase in overall pupil size but decrease in ICA in a dual task setting. To further investigate this, we systematically tested two new dual-task combinations, combining both language comprehension and simulated driving with a memory task. Our findings confirm that more difficult linguistic processing is reflected in a larger ICA. More importantly, however, the dual task settings did not result in an increase in the ICA as compared to the single task, and, consistent with earlier findings, showed a significant decrease with a more difficult secondary task. This contrasts with our findings for pupil size, which showed an increase with greater secondary task difficulty in both tasks. Our results are compatible with the idea that although both pupillometry measures are indicators of cognitive load, they reflect different cognitive and neuronal processes in dual task situations.